The Impact of Developmental Programmes on the Entrepreneurial Attitude of Potential Entrepreneurs in Raipur City - Gupta, Shilpi (Prabandhan: Indian Journal of Management, 2013)
This study was carried out to explore whether developmental programmes organized by various universities improve the inherent entrepreneurial attitudes amongst the potential entrepreneurs. The scope of the study was limited to Raipur City (C.G). The sample of the study was confined to 28 MBA students of an autonomous private college. Questionnaires were distributed to the students and their pre-training and post-training scores were calculated and measured. The entrepreneurial attitudes were measured on four sub-scales: i.e. Achievement motive, Innovativeness, perceived Personal Control and perceived Self-Esteem. The pre - developmental and post - developmental differences in responses were analyzed by using the Likert scale and further conclusions were drawn by applying the paired t - test. The time period of the study was three months. The major finding of the research was that the developmental sessions did have a positive impact on the overall entrepreneurial attitude amongst the potential entrepreneur.